Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

For each problem, information is given related to a linear relationship. Use the given information to write an algebraic rule for the linear relationship. Write the rule in the form indicated.
50 points and brainly.​


For Each Problem Information Is Given Related To A Linear Relationship Use The Given Information To Write An Algebraic Rule For The Linear Relationship Write Th class=

Sagot :

Answer:

  • a) y = 4x - 2
  • b) y = 3x + 2
  • c) y = 2x - 6

Step-by-step explanation:

a)

The slope as per two ordered pairs (-2, -10), (0, -2)

  • m = (-2 - (-10))/(0 - (-2)) = 8/2 = 4

The y-intercept is -2

The equation for this function:

  • y = 4x - 2

b)

The slope is

  • m = 3

The line passes through (1, 5)

The line is:

  • y - 5 = 3( x - 1) in point-slope form
  • y = 3x +2 in slope-intercept form

c)

The slope as per points on the graph (3, 0), (4, 2)

  • m = (2 - 0)/(4 - 3) = 2

The line in point slope form using point (3, 0):

  • y = 2(x - 3)

The line in slope-intercept form:

  • y = 2x - 6

a) substitute m = 4 and c = - 2 into the slope intercept equation, thus, the equation of the line is y = 4x - 2

The answer is y = 4x - 2

b) Let's begin by listing out the given information:

The line has a slope of 3

The equation of the line becomes:

[tex]y = mx + b \\ m = 3 \\ y = 3x + b[/tex]

The line passes through point (1, 5).

We will obtain the equation using the point-slope formula, we have:

[tex]y - y1 = m(x - x1) \\ (x1 \: y1) = (1 \: 5) \\ y - 5 = 3(x - 1) \\ y - 5 = 3x - 3 \\ y = 3x - 3 + 5 \\ y = 3x + 2[/tex]

Therefore, the equation of the straight line is y = 3x + 2

c) we use that point and the slope to replace in the expression:

[tex]y - y1 = m(x - x1)[/tex]

That is:

[tex]y - 0 = 2(x - 3) \: \: y = 2x - 6[/tex]

y = 2x - 6 is the answer